Efficacy of Fenestration Technique for Lumbar Disc Excision in Pain Relief - Jawad Jan Arif, Subhan Shahid, Tanveer Afzal, Muhammad Abubakar, Ali Irfan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the outcomes of lumbar disc excision by fenestration technique for pain relief in lumbar radiculopathy due to prolapsed intervertebral disc. Methodology: This is a descriptive study conducted in a joint venture of orthopedic and neurosurgeons in a private hospital of Lahore. Study was completed in six months duration from July to December 2022. All patients presenting with lower back pain, straight leg raise test positive on <60 degrees and prolapsed disc at the level of L4/L5 or L5/S1 L discs on MRI. Those with multilevel disc prolapse, previous history of spinal surgery, cauda equine syndrome and patients with lumbar stenosis were excluded from the study. All study patients were operated under general anesthesia in knee chest position. Efficacy of the procedure was determined using Dennis Pain Scale. Important findings were documented when patient was discharged. SPSS version 20 was used for statistical analysis. Results: 125 patients were studied including 73(58.4%) males and 52(41.6%) females. Patients with the age of 20-60 years were included in this study with the mean age of 47.3 ± 5.2 years. Most commonly involved disc level was L4-L5 in 77(61.6%) and L5-S1 in 48(38.4%) cases. Unilateral radicular pain was present in 94(75.2%) cases and bilateral pain was present in 31(24.8%) cases. According to Dennis Pain Scale out of 125 cases 78(62.4%) patients presented in Dennis pain scale P4 and among them complete recovery achieved in 70(89.7%) cases. Conclusion: Surgical intervention is necessary in selected patients with prolapsed intervertebral disc with chronic unilateral or bilateral radicular pain. Fenestration technique for disc excision is a very good procedure for prolapsed disc. Keywords: Sciatica, Disc Excision, Prolapsed Disc, Radiculopathy